Design and tuning Cr3+-doped near-infrared phosphors for multifunctional applications via crystal field engineering. Issue 6 (19th January 2022) - Yu, Shuaishuai; Wei, Zhiting; Wu, Junxiao; Wang, Tianli; Zhang, Jia; Luo, Xingliang; Li, Yanyan; Wang, Chuang; Zhao, Lei
Abstract : The full width at half maximum is increased by introducing Sc 3+ regulating the crystal field environment around Cr 3+ in SrGa12 O19 :Cr 3+ . Meanwhile, a promising application potential in night vision lighting and bioimaging has been demonstrated. Abstract : Nowadays, near-infrared (NIR)-emitting luminescence materials with broad application prospects have drawn great attention. SrGa12 O19 :Cr 3+ is a new type of solid light source material that emits NIR light with wide application prospects. However, the narrow full width at half maximum (FWHM) restricts its further multifunctional applications. Therefore, we propose a novel methodology to increase the FWHM by artificially adjusting the strength of the crystal field by doping Sc 3+ ions. By employing Rietveld refinement results, parameters evolution and Raman spectra, Sc 3+ ions are proved to successfully occupy the Ga 3+ crystallographic sites. Combining the spectroscopy characteristics, it was confirmed that the FWHM was increased from 78 nm (127 977 cm −1 ) to 104 nm (96 739 cm −1 ) with the optimum quantum efficiency of 96.55%. In addition, the excellent thermal stability and unprecedented suitability to a 450 nm blue-chip indicate that it is a potential luminescent material candidate for fluorescence conversion NIR light-emitting diode (LED). Finally, the successful implementation of the night vision on vegetation, biological imaging of human tissue and food inspection for different pork portions illustrate the strong commonality of the method.